Effectiveness and safety of immune checkpoint inhibitors in combination with palliative radiotherapy in advanced melanoma: A systematic review. (November 2021) - Ben Shimol, Jennifer; Guzman-Prado, Yuli; Karlinskaya, Maria; Davidson, Tima
Graphical abstract: Highlights: Palliative radiotherapy is commonly added to immunotherapy in advanced melanoma. The combination enhances objective response, complete response and local control. Survival outcomes were mixed with improvements in part of the studies. No increased adverse events or immune related adverse events seen. Abstract: Background: Radiotherapy is frequently added to immune checkpoint inhibitors (ICI) when treating melanoma. We sought to describe the efficacy of combination ICI and palliative radiotherapy (pRT) and assess safety, focusing on immune related adverse events (irAE). Methods: A systematic search for studies investigating the combination of pRT and ICI was conducted. Results: Five hundred-two articles were identified; nine met inclusion criteria. Improvements in objective response rate (p = 0.02), complete response (p = 0.04), and one-year local control (p < 0.005) were demonstrated when pRT was added to ICI. While some studies revealed improved overall and progression free survival, findings were mixed. No significant increases in adverse events or irAE were seen with the combined treatment compared with ICI alone. Conclusion: The included studies revealed that the addition of pRT to ICI is effective and safe in patients with advanced melanoma. Measures of survival varied. More studies are warranted to identify optimal conditions for combination treatment.